2018
DOI: 10.1186/s42397-018-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in spatiotemporal distribution of canopy light interception in relation to yield formation in cotton

Abstract: Background: Within-canopy interception of photosynthetically active radiation (PAR) impacts yield and other agronomic traits in cotton (Gossypium hirsutum L.). Field experiments were conducted to investigate the influence of 6 cotton varieties (they belong to 3 different plant types) on yield, yield distribution, light interception (LI), LI distribution and the relationship between yield formation and LI in Anyang, Henan, in 2014 and 2015. Result: The results showed that cotton cultivars with long branches (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…If leaf area is small, though the light conditions are satisfied, the total photosynthetic products cannot meet the needs of boll growth, both situations lead to low yield of cotton [45]. A highly significant relationship was found between iPAR and leaf area, which is in strong agreement with previous studies [14,24,31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…If leaf area is small, though the light conditions are satisfied, the total photosynthetic products cannot meet the needs of boll growth, both situations lead to low yield of cotton [45]. A highly significant relationship was found between iPAR and leaf area, which is in strong agreement with previous studies [14,24,31].…”
Section: Discussionsupporting
confidence: 89%
“…Spatial distribution of light interception by cotton growing at different densities is of great importance, as light interception directly affects photosynthesis and influences biomass and yield [31]. The traditional method to estimate the vertical direction of light interception in the crop canopy is Beer's law [32], however, leaf angle and leaf curve are needed to simulate the model to calculate PAR distribution of different height of the canopies and contains a series of mathematical functions which are difficult to measure and calculate [33].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned study showed varietal differences in a light interception by the canopy at the squaring stage and maximum differences at the flowering and boll setting. The study by Xing et al (2018) also reported a significant positive relationship between light interception and biomass accumulation among different cotton varieties with the highest biomass accumulation in loose type varieties and the lowest in compact type cotton varieties. Bai et al (2016) evaluated 10 cotton cultivars differing in canopy architecture and reported the maximum biomass accumulation and the highest…”
Section: Introductionmentioning
confidence: 82%
“…The fraction of incoming solar radiation intercepted by the canopy is a function of the leaf area index, canopy structure, and the efficiency with which leaves intercept solar radiation, referred to as the light extinction coefficient (Cirilo et al, 2009;Lantinga et al, 1999;Massignam et al 2009;Plénet et al 2000). A study by Xing et al (2018) with six different cotton varieties differing in canopy structure (compact or loose) reported significant differences in canopy light interception among different cotton varieties. The study reported lower light interception by compact-type cotton cultivars, compared to loose-type cotton cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced LAI is attributed to the increased carbon assimilation rate conferred by plant toppings ( Nie et al., 2021 ). In addition to photosynthesis, plant topping also strongly regulates source–sink photoassimilate partitioning ( Xing et al., 2018 ; Nie et al., 2020 ). Unlike non-topping and chemical topping, manual topping significantly diverts more photoassimilates towards the FB-sourced bolls, and less assimilate to the redundant cotton bolls, making manual topping more advantageous than chemical topping ( Nie et al., 2021 ).…”
Section: Effects Of Source–sink Regulation On Growth and Development ...mentioning
confidence: 99%